Study of risk factors for relapse in frequently versus infrequently relapsing nephrotic syndrome in 1-18 year age group: a combined prospective retrospective cohort analytical observational study - Minj, Simpal Shalini; Rathi, Surbhi; Kondekar, Santosh; David, Jane J. E. (International Journal of Contemporary Pediatrics, 2019)
Background: Early prediction and prevention of risk factors is the key to successful management of childhood nephrotic syndrome. This study was carried out to find the risk factors of relapse which will help in early prediction and reduce the risk of relapse in childhood nephrotic syndrome. Methods: It was a combined prospective-retrospective cohort analytical observational study of duration 18 months with sample size of 80 patients of age group 1-18 years who fulfilled the inclusion and exclusion criteria. The variables taken into account for the present study were demographic and disease related. Results: In the present study, 67.7% of patients with ≤6 year of age at first onset were frequent relapsers while 60% of patients with >6 year of age at first onset were infrequent relapsers. A 77.1% of patients belonging to lower socioeconomic strata and 60% of patients belonging to lower-middle socioeconomic strata were frequent relapsers. 100% of patients having ≥ 4 relapses within the 1st year after diagnosis were frequent relapsers while 73.2% of patients having ≤3 relapses within the same period were infrequent relapsers. In present study, out of 38 patients who had received 8 weeks of steroid therapy 92.1% were frequently relapsing while out of 42 patients who received 12 weeks of steroid therapy 64.3% were found to be infrequently relapsing. Conclusions: Younger age at first onset, higher number of relapses in first year and lower socio-economic strata is associated with frequently relapsing nephrotic syndrome. Longer duration of steroid therapy (12 weeks) lowers the chance of frequent relapses.